IMPLEMENTATION OF THE LEARNING MODEL USING THE ALI METHOD TO IMPROVE THE ABILITY TO READ THE QUR'AN FOR STUDENTS OF THE SPECIAL PROGRAM FOR TAHFIZHUL QUR'AN (PKTQ) SUKOHARJO 2 STATE ELEMENTARY SCHOOL (MIN) 2022/2023 - Arrohman, Syauqu Rofiq; Fatimah, Meti; Khasanah, Uswatun (Proceeding of International Conference of Islamic Education, 2023)
The 'Ali method is a way of reading the Qur'an by using keywords, movements and tartil. This method is very easy to understand by children, teenagers and even parents as beginners learning to read the Qur'an. In the process of reading the Qur'an, many students experience difficulties and mistakes, so it is necessary to motivate them to be diligent in reading the Qur'an and it is also necessary to see what factors are the cause, for the need to conduct research in the Special Program Tahfizhul Qur'an (PKTQ) Madrasah Ibtidaiyah Negeri (MIN) 2 Sukoharjo. This research aims to find out how the implementation of the 'Ali method in improving the ability to read the Qur'an in the Special Program for Tahfizhul Qur'an (PKTQ) MIN 2 Sukoharjo. To find out how the implementation of the 'Ali method in PKTQ MIN 2 Sukoharjo in improving the ability to read the Qur'an, the author collects theories about the 'Ali method in reading the Qur'an. This research is qualitative by collecting data using interviews, observation and documentation. To increase the degree of data validity, data validity testing is carried out by extending participation, persistence, observation, triangulation and using reference materials. The process of analyzing the data is done with three streams, namely: data reduction, data presentation and verification (conclusion). The research conducted resulted in the final analysis of the implementation of the 'Ali method in improving the ability to read the Qur'an in the Special Program for Tahfizhul Qur'an (PKTQ) MIN 2 Sukoharjo, namely in teaching the teacher is quite good at mastering the material and learning steps with the 'Ali method, although not all teachers are nationally certified. This method is very good because it makes students able to quickly read the Qur'an with the correct makhroj and tajweed. The author can conclude that the implementation of the 'Ali method in improving the ability to read the Qur'an in the Special Program for Tahfizhul Qur'an (PKTQ) MIN 2 Sukoharjo runs well and correctly and gets maximum results.